Impact of Unpredictable Stress Factors of the Global Economy on the Functioning of the Digital Ecosystem of the Region - Vladimir Sergeevich KRIVOSHLYKOV; Nikolay Vladimirovich ZHAKHOV; Natalya Petrovna BRATISHKO; Olga Vladimirovna EMELYANOVA; Mikhail Viktorovich SHATOKHIN (Communications of International Proceedings, 2020)
This article examines the impact of the economic crisis caused by the COVID-19 pandemic on the structure of the regional economy (using the example of five subjects of Central Russia). As a result of the study, opposite trends were identified, namely, the growth of industrial production of basic food products (meat, milk, bread) in large agricultural organizations and a reduction in the total effective demand of the population of these regions due to a decrease in real disposable income (due to inflationary processes in the economy). The most realistic scenario for the development of the current situation in the regional economy is stagnation and an increase in the decline in the welfare of the population.
Keywords: Regional Economy; Economic Crises; Digital Economy; Food Sector; Production Indices; COVID-19.